Prevalence rate and course of symptoms of Disruptive Mood Dysregulation Disorder (DMDD) - Grau, Katharina; Plener, Paul L.; Hohmann, Sarah; Fegert, Jörg M.; Brähler, Elmar; Straub, Joana (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2017)
Objective: According to DSM-5, Disruptive Mood Dysregulation Disorder (DMDD) is characterized by chronic temper outbursts and irritable moods. So far, little is known about its prevalence rate, course and influence on individual well-being. We assessed the prevalence rates of DMDD symptoms during adulthood and primary school age - the latter retrospectively - and studied their relationship with psychiatric disorders and socioeconomic variables. Methods: A total of 2,413 subjects, aged 18-94 years, participated in this population-based, representative study based on self-reports. Results: 12 (0.50 %) subjects reported elevated DMDD symptoms during adulthood, and 19 (0.79 %) reported elevated DMDD symptoms during primary school age. DMDD symptoms were associated with higher rates of depression and anxiety symptoms. Those reporting elevated DMDD symptoms during adulthood were more often single or divorced, and those reporting elevated DMDD symptoms during primary school age were more often childless and unemployed during adulthood compared to subjects without DMDD symptoms. Conclusions: DMDD symptoms seem to show a chronic course and go hand in hand with elevated psychiatric symptoms and impaired socioeconomic and demographic status.
Gesehen am 04.05.2018